Should Proton Pump Inhibitors be Systematically Prescribed in Patients With Esophageal Atresia After Surgical Repair?. Issue 1 (July 2019) - Righini Grunder, Franziska; Petit, Laetitia-Marie; Ezri, Jessica; Jantchou, Prevost; Aspirot, Ann; Laberge, Sophie; Faure, Christophe
ABSTRACT: Objective: To evaluate outcomes of patients with esophageal atresia (EA) on systematic treatment with proton pump inhibitors (PPI) since the neonatal period and to determine factors associated with successful discontinuation of PPI. Study design: Longitudinal cohort study with prospective data collection of 73 EA patients, over 11 years systematically treated with PPI. Outcome and predictive factors for discontinuation of PPI treatment were evaluated at study end in February 2017. The incidence of anastomotic strictures was compared with a historical cohort of 134 EA patients followed in the same institution between 1990 and 2005 before the era of systematic PPI treatment. Results: PPI treatment was discontinued definitively in 48% of patients during follow-up. Prematurity, longer initial hospitalization, moderate-to-severe tracheomalacia, anastomotic leak and anastomotic stricture had a significant negative association with PPI discontinuation on univariate analysis ( P < 0.05). On adjusted multivariable Cox regression analysis, moderate-to-severe tracheomalacia and anastomotic leak were negatively associated with discontinuation of PPI treatment (hazard ratio 0.26 [95% CI 0.12–0.59]; P = 0.001 and hazard ratio 0.38 [95% CI 0.16–0.93]; P = 0.03, respectively). There was no significant difference in the incidence of anastomotic strictures in the present cohort compared with the historical cohort (44% vs 39%); ( P > 0.05). Conclusions: PPI treatment does not prevent the formation of anastomotic strictures and appears to be over-prescribed in children with airway symptoms because of tracheomalacia. This suggests that PPI treatment could be prescribed more selectively. Close monitoring and long-term follow-up, however, of these vulnerable patients in specialized multidisciplinary clinics is imperative. Abstract : Supplemental Digital Content is available in the text